Partial jejunal diversion using an incisionless magnetic anastomosis system: 1-year interim results in patients with obesity and diabetes - Machytka, Evžen; Bužga, Marek; Zonca, Pavel; Lautz, David B; Ryou, Marvin; Simonson, Donald C; Thompson, Christopher C (Gastrointestinal endoscopy, 2017)
BACKGROUND AND AIMS: Most patients with type 2 diabetes mellitus have obesity. Studies show that bariatric surgery is superior to medical treatment for remission of type 2 diabetes mellitus. Nevertheless, very few patients undergo surgery, and a less-invasive endoscopic alternative is desirable. METHODS: This was a single-arm first-in-human pilot study designed to evaluate the technical feasibility, safety, and clinical performance of the incisionless magnetic anastomosis system (IMAS) to create a partial jejunal diversion (PJD). Ten patients with obesity and type 2 diabetes mellitus, prediabetes, or no diabetes were enrolled. A PJD to the ileum was attempted in all patients under general anesthesia. The IMAS was delivered through the working channel of a colonoscope, with laparoscopic supervision. The patients were not required to participate in an intensive lifestyle/diet management program. Endoscopic visualization of the anastomosis was obtained at 2, 6, and 12 months. Patient weight, glycemic profile, and metabolic panels were acquired at 0.5, 1, 2, 3, 6, 9, and 12 months. RESULTS: A PJD was created in all patients with no device-related serious adverse events. The anastomosis remained widely patent in all patients at 1 year. Average total weight loss was 14.6% (40.2% excess weight loss at 12 months). A significant reduction in glycated hemoglobin level was observed in all diabetic (1.9%) and prediabetic (1.0%) patients, while reducing or eliminating the use of diabetes medications. CONCLUSIONS: Permanent anastomosis for PJD was created in all patients with the IMAS. This resulted in improvement in measures of hyperglycemia and progressive weight loss. (Clinical trial registration number: NCT02839512.).
Keywords: dospělí; magnety; Female; Magnets; Bariatric Surgery; Adult; ženské pohlaví; Diabetes Mellitus, Type 2; Obesity; lidé; Blood Glucose; Prediabetic State; anastomóza chirurgická; Hypoglycemic Agents; Pilot Projects; diabetes mellitus 2. typu; pilotní projekty; gastrointestinální endoskopie; jejunum; hypoglykemika; prospektivní studie; Endoscopy, Gastrointestinal; obezita; Male; Prospective Studies; Anastomosis, Surgical; bariatrická chirurgie; Jejunum; glykovaný hemoglobin; lidé středního věku; mužské pohlaví; krevní glukóza; Glycated Hemoglobin; Middle Aged; prediabetes; Humans